2019
DOI: 10.1002/fsn3.883
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable consumption, leisure‐time physical activity, and sedentary behavior among children and adolescent students in Uganda

Abstract: Introduction Fruit and vegetable (FV) intake and participation in leisure‐time physical activity (PA) and in sedentary behavior in accordance with the recommendations are met in a minority of populations including children and adolescents. Objective To describe the frequency of FV intake, leisure‐time PA, and sedentary behavior, assess compliance with international recommendations, and how selected factors are associated with these recommendations. Methods The FV consumption and PA questionnaire items previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 32 publications
6
21
3
2
Order By: Relevance
“…Whiles there was no clear difference between adults and children for meat consumption, it was found that consumption decreased with age for fruits (Table 10) and for vegetables (Table 9). This finding is in line with findings from studies by Ndagire et al (2019) 166 in Uganda, 166 for fruits in Tanzania 167 and in the UK based on National Diet and Nutrition Survey (NDNS). 187 Conversely, studies from Tanzania 167 have reported higher vegetable intakes in the old than in younger populations.…”
Section: Mfv Consumption By Age Cohort and Dietary Assessment Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…Whiles there was no clear difference between adults and children for meat consumption, it was found that consumption decreased with age for fruits (Table 10) and for vegetables (Table 9). This finding is in line with findings from studies by Ndagire et al (2019) 166 in Uganda, 166 for fruits in Tanzania 167 and in the UK based on National Diet and Nutrition Survey (NDNS). 187 Conversely, studies from Tanzania 167 have reported higher vegetable intakes in the old than in younger populations.…”
Section: Mfv Consumption By Age Cohort and Dietary Assessment Methodssupporting
confidence: 91%
“…164,165 On the contrary, fruit or/and vegetable intake remain substantially below WHO recommended levels (Figures 6 and 9). Similar findings of less than 1 portion of fruit or vegetables have been reported in Ghana, 98 Uganda, 166 Tanzania 167 and other low-income countries (LICs) like Bangladesh, India, Jamaica, and Philippines. 168 The prevalence of low fruit intakes (less than 1 portion daily) was in a similar range as those reported by other studies conducted in some highincome countries.…”
Section: Mfv Consumption Trends Between and 2015supporting
confidence: 73%
“…In a group of adolescents in Sudan, we can see 3.8% of "Under 30 minutes" responses, and 26.2% of negative responses ("I don't do any physical activity"). At the opposite end, 51.0% are adolescents doing sports for over 60 minutes per day (Misaa, Somiya, & Siham, 2018 (Ndagire, Muyonga, & Nakimbugwe, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In a Ugandan adolescents study, 8.86% of negative responses appeared -they did not eat vegetables in the last 30 days (Ndagire, Muyonga, & Nakimbugwe, 2019).…”
mentioning
confidence: 98%
“…The extent to which information accessed through these different channels has resulted in improved diets has not been adequately investigated in South Africa. While studies have looked at the determinants of F+V consumption in South Africa [14][15][16]28] and in other developing countries [29][30][31][32], these have generally not investigated the effect of information access. There is growing literature [33][34][35] that links access to information through mobile phones to nutrition.…”
Section: Introductionmentioning
confidence: 99%